PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE NUMBER HEAD TOGETHER PADA SISWA KELAS V SDN 219/II BTN LINTAS ASRI KECAMATAN BUNGO DANI - Nurlev Avana; Tri Wiyoko; Aulia Wulandari (Jurnal Tunas Pendidikan, 2020)
This study aims to improve the learning outcomes of mathematics in class V students. This research was conducted at SDN 219/II BTN Lintas Asri District Bungo Dani. This type of research is a classroom action research (PTK) carried out in collaboration with researchers and class teachers V grade student SDN 219/II BTN Lintas Asri consisting of 20 students. This study uses a number head together (NHT) model, this study was conducted in two cycles, the data collection methods used were tests and observations. Collected data were analyzed qualitatively and quantitatively. The results showed an increase in student learning outcomes after the teacher applied the NHT learning model in integer arithmetic operations. In the first cycle the percentage of completeness of learning outcomes is 55% of students who have not completed 45%. In cycle II students learning completeness increased to 85% and students who were not yet 15% complete. As well as the result of observations of student activity has increased in cycle I that is 66% in cycle II to 91%.